Impact of European Black Carbon on East Asian Summer Climate - Jiang-Hua, Wan; Mahmood, Rashed; Shuanglin, Li (Atmospheric and oceanic science letters = Daqi-he-haiyang-kexue-kuaibao, 2013)
The remote response of the East Asian summer monsoon (EASM) to European black carbon (EUBC) aerosols was studied by using an ensemble of sensitivity experiments with the Geophysical Fluid Dynamics Laboratory (GFDL) atmospheric general circulation model (AGCM) Atmospheric Model version 2.1 (AM2.1). The results show that EUBC causes an enhanced EASM. The resulted enhanced southwesterly brings more moisture supply from the Bay of Bengal, which causes an increase in precipitation over the Yangtze River valley, northeastern China, the eastern part of the Yellow River valley, and the Tibetan Plateau. Diagnostic examination suggests that EUBC induces enhanced tropospheric heating over most of the Eurasian Continent through a propagating wave train and horizontal air temperature advection. This phenomenon results in intensified thermal contrast between land and ocean, which accounts for the enhanced EASM. Moreover, reductions in EUBC emission in 1992 may have contributed to decadal weakening of the EASM in the early 1990s.